Exploring the Effects of Technological Advancements on Hotel Guests and Employees in Metro Manila: A Comparative Study - Jose Ehvenzer P Legaspi; Isabel Andrea D Huerto; Ma Pauline L Advincula; Ranyel C Taperla; Jocelyn Y. Camalig (Research Synergy Foundation, 2023)
The guests and employees of a 3-star hotel in Metro Manila share a similar perspective on the technological advancements that are being implemented and made available in their establishments. These technological advances have a positive impact on both guests and employees as they greatly improve their stay in the hotel. Although the survey identified some issues, they were mostly rated as moderate by both guests and staff, which suggests that they can be minimized or resolved. Furthermore, there was a significant difference in the impact of technological advances on guests and employees. This highlights the need for the hospitality industry to embrace technological advances in order to provide guests with improved services and employees with the tools they need to work more efficiently. However, it is important to note that this study has some limitations. It only covers guests and employees in a 3-star hotel, which may not be representative of all hotels in the area. Therefore, it is recommended to widen the scope of the study to include hotels with 4 and 5-star ratings to gain a more comprehensive understanding of the subject. Further studies could also examine how technological advances impact the hotel's bottom line and the overall guest experience.